Stimulasi Perkembangan Motorik Kasar Anak Usia Dini Melalui Permainan Tradisional “Gobak Sodor”: Lanny Wijayaningsih - Lanny Wijayaningsih (Social Philanthropic, 2023)
The development of child motor skill as a part of importance things in golden age stage, so they need stimulation for moving and it is used to do many activities in their daily life. The aim of this research is to stimulate the development motoric early child through traditional game from central “gobag sodor” the method of this research is descriptive qualitative, that described the datas in detail and systematically and also based on the real fact in the students of early child education lab school UKSW. The resource datas is from articles, journals and text books, the primer datas are from observation the students and questioners to the teachers and parents, the result of this research, the traditional game gobag sodor that plays in many times to early child can improve the motoric skill very well. And the students look more flexible gross in their moving, their speed balance and the aqility of students in playing gobag sodor.